2021
DOI: 10.2478/sjecr-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Pharmacological Properties of Allium Ursinum

Abstract: Allium ursinum L. is a perennial herbaceous plant belonging to the Alliaceae family. Several classes of bioactive compounds have been isolated from A. ursinum so far, among them sulfur and phenolic compounds as quantitatively the most distributed constituents, responsible for pharmaceutical eff ects of the plant. Small amounts of steroidal glucosides, lecitins, fatty acids and several amino acids, as well as the essential oil are also present in A. ursinum. This plant species is characterized by a long history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…In addition to the cysteine sulfoxide pattern and volatile profile, wild garlic also shares similarities with garlic in the amino acid profile [3,4,56]. According to several authors, the main amino acid in wild garlic is arginine, followed by aspartic acid, glutamic acid, methionine, threonine, valine, leucine, proline, and glycine [4,7,57]. Our study showed that the same amino acids were found to be abundant, although not in the order that other authors have reported.…”
Section: Discussionsupporting
confidence: 61%
“…In addition to the cysteine sulfoxide pattern and volatile profile, wild garlic also shares similarities with garlic in the amino acid profile [3,4,56]. According to several authors, the main amino acid in wild garlic is arginine, followed by aspartic acid, glutamic acid, methionine, threonine, valine, leucine, proline, and glycine [4,7,57]. Our study showed that the same amino acids were found to be abundant, although not in the order that other authors have reported.…”
Section: Discussionsupporting
confidence: 61%
“…Extracts prepared from its fresh flowers and leaves exert antifungal and antibacterial activities, directed predominantly on Gram-positive bacteria and less on Gram-negative. The antimicrobial potential of this plant is attributed to sulfur compounds, especially allicin [ 22 ].…”
Section: Introductionmentioning
confidence: 99%